2012
DOI: 10.1016/j.jaci.2012.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Egg-allergic patients can be safely vaccinated against influenza

Abstract: that additional factors are required. Our study also confirmed the association of FLG mutations and early-onset infantile eczema, which is in line with previous work. 6 Our ability to interrogate the role of sensitization in the relationship between FLG mutations and food allergy in a large population-based, age-matched, challenge-proved food allergy cohort is a major and novel strength of this work. There is some potential participation bias among negative control subjects (higher immediate family history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 6 publications
0
27
0
1
Order By: Relevance
“…It was not surprising that there were no immediate IgE-mediated reactions after vaccination of the children with egg allergy because the quantity of ovalbumin in LAIV is comparable with that of TIV, which has previously been shown to be safe in patients with egg allergy. 1,2 Moreover, systemic absorption of ovalbumin via intranasal vaccination is probably much lower than intramuscular administration; a recent study showed that intranasal peanut challenge of patients with documented peanut allergy and with much higher concentration of allergens than those present in LAIV was not associated with systemic reactions. 9 Furthermore, systemic absorption of corticosteroids administered intranasally is much lower than when administered orally.…”
Section: To the Editormentioning
confidence: 99%
“…It was not surprising that there were no immediate IgE-mediated reactions after vaccination of the children with egg allergy because the quantity of ovalbumin in LAIV is comparable with that of TIV, which has previously been shown to be safe in patients with egg allergy. 1,2 Moreover, systemic absorption of ovalbumin via intranasal vaccination is probably much lower than intramuscular administration; a recent study showed that intranasal peanut challenge of patients with documented peanut allergy and with much higher concentration of allergens than those present in LAIV was not associated with systemic reactions. 9 Furthermore, systemic absorption of corticosteroids administered intranasally is much lower than when administered orally.…”
Section: To the Editormentioning
confidence: 99%
“…85 However, the greatest attention recently has been to the administration of influenza vaccines for persons with egg allergy. 86 Des Roches et al 87 combined their results with those of 26 other studies that included more than 25 patients with egg allergy receiving the influenza vaccine. The summary included 4172 patients (513 with severe allergy) receiving a total of 4729 doses without anaphylaxis, indicating a risk of anaphylaxis (95% CI) of 0% to 0.08% (95% CI among those with severe egg allergy, 0% to 0.66%).…”
Section: Drug Allergymentioning
confidence: 99%
“…Such results did not significantly differ from the rate in non-egg-allergic controls [17,37,38]. The majority of these studies specifically included patients with histories of severe anaphylaxis (n=656) as a result of egg ingestion.…”
Section: Allergic Reactions To Egg Proteinmentioning
confidence: 85%